السوق السياحي في سورية وحجم الطلب على المنتج السياحي السوري - عكروش محمد; زهيري علاء الدين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
نظراً لأوجه القصور التي تعاني منها صناعة السياحة السورية، بسبب الاهتمام المتأخر بهذه الصناعة، وما نتج عنه عدم اكتمال البنية التحتية اللازمة، وانخفاض مستوى الطلب السياحي الدولي رغم تحسنه في السنوات الأخيرة. فإن دراسة السوق السياحي القائم في سورية، من حيث المنشآت السياحية القائمة والأنماط السياحية التي يمكن تسويقها، بالإضافة إلى دراسة جانب الطلب السياحي الدولي والداخلي من حيث نموه ومصادره والأهمية النسبية التي تمثلها المجموعات السياحية في الطلب على المنتج السياحي السوري. قد تسهم مستقبلاً في العمل على حسن استثمار هذا السوق من خلال زيادة الاهتمام بالمنشآت السياحية القائمة وتطويرها، والعمل على خلق أنماط سياحية جديدة، و زيادة الطلب الدولي والداخلي على المنتج السياحي السوري. Because of the problems Syrian tourism industry faces, due to the late attention paid to this industry , and its result such as the provided tourist services being incomplete and the low international tourism demand , though it has improved in the last years, the study of the tourist market existed in Syria in terms of the existed tourist institutions, and kinds of provided tourist services, in addition to the study of the international and local tourist demand concerning its growth, resources, and its relative importance represented by the tourist groups for the demand on the Syrian tourist product. This study may help to provide a good investment of this market by increasing the attention paid to available tourist institutions and improving it, and the work to create new tourist forms, and consequently increasing the international and local demand of the Syrian tourist product.